A Comprehensive Review on Transdermal Delivery of Nanosponges - Poonam, Raut; Prakash, Jadhav; Priyanka, Sangar; Vivekkumar, Redasani; Nikita, Bhosale; Varda, Joshi (Asian Journal of Pharmaceutical Research and Development, 2023)
The field of innovative medication delivery has greatly benefited from nanotechnology and miniaturisation, which have also transformed the potential in the current healthcare industry. The design of nano-scale drug carriers using various nanotechnology-based approaches for the delivery of lipophilic drug molecules is the current trend in novel drug delivery-based research. Nanotechnology and miniaturisation, which have also changed the possibilities in the contemporary healthcare business, have tremendously helped the field of inventive medicine distribution. Targeting medication distribution in a regulated manner is made possible in large part by NSs. The use of NSs, its preparation, and assessment have all been covered in this review paper. The healthcare industry is seeing encouraging results from a variety of nanosponges formulations, including parenteral, topical, oral, and inhalation, which offer enormous promise for future development and study.